TEMPO-mediated aliphatic C–H oxidation with oximes and hydrazones - Zhu, Xu (2013)
A method for aliphatic C–H bond oxidation of oximes and hydrazones mediated by 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) has been developed, which enables the concise assembly of substituted isoxazole and pyrazole skeletons.